Evaluation of the viscoelastic properties of lower-extremity muscles of pediatric hemophilia patients using myotonometric measurements - Gönen, Tuğba; Usgu, Serkan; Yakut, Yavuz; Akbayram, Sinan; Yakut, Yavuz; Usgu, Serkan; Gönen, Tuğba (Multidisciplinary Digital Publishing Institute (MDPI))
This study aimed to evaluate the viscoelastic properties of lower-extremity muscles in pediatric hemophilia (FVIII-IX) patients. The study included 20 severe- and moderate-type right-dominant hemophilia patients diagnosed with hemophilia A–B and 20 healthy children. Viscoelastic properties (tone, stiffness, elasticity) of the lower-extremity muscles were measured using a MyotonPRO device. The physical characteristics of the pediatric hemophilia patients (mean age: 11.9 ± 3.95 years) and the control group (mean age: 12.6 ± 3.41 years) were found to be similar. A difference was observed only in the elasticity of the right vastus lateralis (p < 0.05) by means of the viscoelastic properties of the lower-extremity muscles. The results were similar in other muscle groups (p > 0.05). The dominant-side vastus lateralis muscle elasticity (the ability of the muscle to regain its original shape after contraction or removal of an external force) of hemophilia patients was found to be lower compared to healthy children. The fact that 45% of hemarthroses occur in the knee joint and that recurrent bleeding may affect the flexibility of the vastus lateralis, which is the main muscle within the quadriceps muscle group and responsible for the stabilization of the patella, can be associated with the study results. © 2024 by the authors.
Keywords: elasticity; hemarthrosis; hematoma; hemophilia; stiffness; tone